Hubungan Stres Terhadap Berat Badan dan Tekanan Darah pada Masyarakat di Daerah Perbatasan Kalimantan Utara - Hotlan, Hotlan; Pujianto, Ahmat; zulfia, Rahmatuz; Handayani, Fitriya; Nugraha, M. Akbar (Pustaka Galeri Mandiri, 2025)
Stress plays a crucial role in affecting both mental and physical health, potentially contributing to changes in body weight and blood pressure. This study aims to explore the relationship between stress levels and body weight, as well as blood pressure, among the community living in the northern border region of Kalimantan, particularly in Sebatik Island. The research employs a quantitative approach with a cross-sectional design, involving 300 participants from the border community. The study has received ethical approval, as indicated by the letter number 113/KEPK-FIKES UBT/XI/2024. The results indicate a significant relationship between stress and body weight (p=<0,001), stress and systolic blood pressure (p=<0,001), as well as stress and diastolic blood pressure (p=<0,001). The instruments used for measurement include the DASS version 21, sphygmomanometer, and anthropometric scales. These findings are expected to contribute to the development of more effective mental health programs and evidence-based interventions. Furthermore, this study is anticipated to serve as a reference for future research in the field of psychiatric nursing in border areas, and be beneficial to both the public and educational institutions in understanding the impact of stress on physical health.